Preparation method and flame-retardant application of modified montmorillonite

Through the coordinated modification of montmorillonite by phosphoric acid and dodecylamine, the problem of insufficient hydrophilicity and flame retardant properties of montmorillonite in the organic system is solved, and its hydrophobicity and flame retardant properties in polymer matrix are improved. Performance, significantly improves the mechanical and flame retardant properties of composite materials.

CN119177034APending Publication Date: 2024-12-24SUZHOU TIANMAI THERMAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411300533.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Montmorillonite has insufficient hydrophilicity and natural flame retardant properties in organic systems, which limits its application in polymer matrix.

Method used

Through the coordinated modification of montmorillonite by phosphoric acid and dodecylamine, it improves its hydrophobicity and introduces flame retardant elements. The ethanol dispersion of montmorillonite is used to promote the chemical reaction between phosphoric acid and montmorillonite surface, and form organic through dodecylamine. to enhance the hydrophobicity of montmorillonite and its interaction with polymers.

Benefits of technology

The uniform dispersion and flame retardant effect of montmorillonite in the polymer matrix are improved, the mechanical properties and flame retardant properties of the composite materials are enhanced, and good hydrophobicity and flame retardant properties are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177034A_ABST
    Figure CN119177034A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and flame-retardant application of modified montmorillonite, and the preparation method comprises the following steps: obtaining raw materials which at least comprise montmorillonite, ethanol, phosphoric acid and lauryl amine; montmorillonite is added into ethyl alcohol and stirred under the first condition, and suspension liquid is obtained; adding phosphoric acid into the suspension, and stirring under a second condition to obtain an activated solution; adding lauryl amine into the activated solution, and stirring under a third condition to obtain a mixed solution containing modified montmorillonite; and separating the modified montmorillonite from the mixed solution. The modified montmorillonite disclosed by the invention has good hydrophobicity and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a preparation method of modified montmorillonite and a flame retardant application thereof. Background Art

[0002] As a layered silicate mineral, montmorillonite has good adsorption and ion exchange properties, but its hydrophilicity limits its application in organic systems, and the flame retardant properties of natural montmorillonite are poor.

[0003] The present invention solves at least one of the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method of modified montmorillonite and its flame retardant application, by synergistically modifying montmorillonite with phosphoric acid and dodecylamine, improving its hydrophobicity and introducing flame retardant elements, thereby optimizing its flame retardant application effect in a polymer matrix.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] The first aspect of the present invention provides a method for preparing modified montmorillonite, characterized by comprising:

[0007] Obtaining raw materials, wherein the raw materials at least include montmorillonite, ethanol, phosphoric acid and dodecylamine;

[0008] Adding the montmorillonite to ethanol and stirring under a first condition to obtain a suspension;

[0009] Adding the phosphoric acid to the suspension and stirring under two conditions to obtain an activated solution;

[0010] adding dodecylamine to the activation solution and stirring under a third condition to obtain a mixed solution including modified montmorillonite;

[0011] The modified montmorillonite is separated from the mixed solution.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] By dispersing montmorillonite with ethanol, its layered structure can be fully developed, increasing the specific surface area, which is convenient for the subsequent activation treatment of phosphoric acid. At the same time, ethanol can inhibit the re-agglomeration of montmorillonite, ensuring the uniformity of the surface reaction in the subsequent modification process; phosphoric acid reacts chemically with the hydroxyl groups on the surface of montmorillonite in the ethanol solution, and the activation treatment makes the montmorillonite have higher surface reaction activity, which promotes the subsequent modification and grafting of montmorillonite with dodecylamine. At the same time, phosphoric acid, as a phosphorus-containing compound, introduces flame retardant elements while taking into account the regulation of hydrophobicity; the long-chain alkyl in the dodecylamine molecule reacts with the negatively charged phosphate group on the surface of montmorillonite to form an organic surface of montmorillonite, thereby enhancing the hydrophobicity of montmorillonite. At the same time, the modification of dodecylamine is conducive to the uniform dispersion of montmorillonite in the polymer matrix, avoiding the agglomeration of montmorillonite, thereby improving the flame retardant effect of the montmorillonite-polymer matrix composite material. The addition of dodecylamine can also enhance the interaction between montmorillonite and polymer, including adhesion and interfacial affinity, and improve the mechanical properties and flame retardant properties of montmorillonite-polymer matrix composites.

[0014] In some possible implementations, by weight percentage, the content of the montmorillonite is 10 wt % to 30 wt %, and the content of the ethanol is 70 wt % to 90 wt %.

[0015] In some possible implementations, the amount of the activator added is 15% to 25% of the montmorillonite content.

[0016] In some possible implementations, the molar ratio of the phosphoric acid to the dodecylamine is 2.5:1 to 3.5:1.

[0017] In some possible implementations, the first condition includes: a stirring temperature of 50 to 70° C. and a stirring time of 30 to 60 min.

[0018] In some possible implementations, the second condition includes: a stirring temperature of 50 to 70° C. and a stirring time of 30 to 60 min.

[0019] In some possible implementations, the third condition includes: a stirring temperature of 50 to 70° C., and a stirring time of 30 to 60 min.

[0020] The second aspect of the present invention provides a flame retardant composite material, comprising modified montmorillonite and a polymer matrix, wherein the content of the polymer matrix is ​​30% of the content of the modified montmorillonite by weight, and the modified montmorillonite is prepared by the above preparation method.

[0021] A third aspect of the present invention provides a method for preparing a flame retardant composite material, comprising:

[0022] Preparing a polymer matrix and the modified montmorillonite obtained by the above preparation method;

[0023] The polymer matrix and the modified montmorillonite are mixed to prepare a flame retardant composite material by a melt blending method;

[0024] In terms of weight percentage, the content of the polymer matrix is ​​30% of the modified montmorillonite. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flowchart of the steps of the method for preparing modified montmorillonite according to an embodiment of the present invention;

[0026] Figure 2 The present invention is a flowchart of the steps of the method for preparing a flame retardant composite material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0027] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make the present invention more comprehensive and complete and to fully convey the concepts of example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their repeated description will be omitted.

[0028] This embodiment provides a method for preparing modified montmorillonite. Figure 1 As shown, it includes steps S1 to S5.

[0029] Step S1: obtaining raw materials, which at least include montmorillonite, ethanol, phosphoric acid and dodecylamine.

[0030] In this embodiment, ethanol is preferably anhydrous ethanol.

[0031] Step S2: adding montmorillonite to ethanol and stirring under a first condition to obtain a suspension.

[0032] As a solvent, ethanol is mainly used to disperse montmorillonite, so that its layered structure can be fully developed, increasing the specific surface area, and facilitating the subsequent activation treatment of phosphoric acid. At the same time, ethanol can inhibit the reagglomeration of montmorillonite and ensure the uniformity of the surface reaction in the subsequent modification process.

[0033] In some embodiments, the first condition includes: a stirring temperature of 50-70°C and a stirring time of 30-60 min. For example, the stirring temperature is 50°C, 60°C, 70°C; and the stirring time is 30 min, 40 min, 50 min, 60 min.

[0034] If the stirring temperature is too high (higher than 70°C), it may cause the decomposition of organic matter and affect the subsequent modification effect; if the stirring temperature is too low (lower than 50°C), it will not be conducive to the dispersion of montmorillonite.

[0035] It should be further explained that the applicant has found that the weight percentage of ethanol and montmorillonite can directly affect the dispersion effect of montmorillonite, thereby affecting the final performance of the hydrophobicity and flame retardancy of the modified montmorillonite. In this embodiment, in terms of weight percentage, preferably, the content of montmorillonite is 10wt% to 30wt%, and the content of ethanol is 70wt% to 90wt%. For example, when the weight of montmorillonite is 10 parts by weight, the weight of ethanol is 90 parts by weight; when the weight of montmorillonite is 20 parts by weight, the weight of ethanol is 80 parts by weight; when the weight of montmorillonite is 30 parts by weight, the weight of ethanol is 70 parts by weight.

[0036] Step S3: adding phosphoric acid to the suspension and stirring under the second condition to obtain an activated solution.

[0037] Phosphoric acid reacts chemically with the hydroxyl groups on the surface of montmorillonite in an ethanol solution, and the montmorillonite is given a higher surface reactivity through activation treatment, which promotes the subsequent modification and grafting of montmorillonite with dodecylamine. At the same time, phosphoric acid, as a phosphorus-containing compound, takes into account the regulation of hydrophobicity while introducing flame retardant elements. It should be further explained that the applicant has found that the content ratio of phosphoric acid to montmorillonite can also affect the final performance of the hydrophobicity and flame retardancy of the modified montmorillonite. In this embodiment, the amount of phosphoric acid added is 15% to 25% of the montmorillonite content, for example, it can be 15%, 20%, or 25%. Preferably, the amount of phosphoric acid added is 20% of the montmorillonite. Within this range, montmorillonite has good hydrophobicity and flame retardancy.

[0038] In some embodiments, the second condition includes: a stirring temperature of 50-70°C and a stirring time of 30-60 min. For example, the stirring temperature is 50°C, 60°C, 70°C; and the stirring time is 30 min, 40 min, 50 min, 60 min.

[0039] If the stirring time is too short, less than 30 min, the hydroxyl groups on the surface of montmorillonite may not be fully activated, thus affecting the subsequent grafting effect of dodecylamine. If the stirring time is too long, more than 60 min, phosphoric acid may self-polymerize.

[0040] Step S4: adding dodecylamine to the activation solution and stirring under the third condition to obtain a mixed solution including modified montmorillonite.

[0041] The long-chain alkyl in the dodecylamine molecule reacts with the negatively charged phosphate on the surface of montmorillonite to form an organic surface of montmorillonite, thereby enhancing the hydrophobicity of montmorillonite. At the same time, the modification of dodecylamine is conducive to the uniform dispersion of montmorillonite in the polymer matrix, avoiding the agglomeration of montmorillonite, thereby improving the flame retardant effect of the montmorillonite-polymer matrix composite material. The addition of dodecylamine can also enhance the interaction between montmorillonite and polymer, including adhesion and interface affinity, and improve the mechanical properties and flame retardant properties of the montmorillonite-polymer matrix composite material.

[0042] In some embodiments, the third condition includes: a stirring temperature of 50-70°C and a stirring time of 30-60 min. For example, the stirring temperature is 50°C, 60°C, 70°C; and the stirring time is 30 min, 40 min, 50 min, 60 min.

[0043] If the time is less than 30 minutes, the grafting of dodecylamine is incomplete, and if the time exceeds 60 minutes, side reactions may occur, thereby reducing the hydrophobicity and flame retardant effects.

[0044] It should be further explained that the applicant has found that the molar ratio of dodecylamine to phosphoric acid can also affect the final performance of the hydrophobicity and flame retardancy of the modified montmorillonite. In this embodiment, the molar ratio of phosphoric acid to dodecylamine is 2.5:1 to 3.5:1, for example, it can be 2.5:1, 3:1, 3.5:1, and preferably, the molar ratio of phosphoric acid to dodecylamine is 3:1. Within this range, the montmorillonite has good hydrophobicity and flame retardancy.

[0045] Step S5: separating the modified montmorillonite from the mixed solution. Specifically, the modified montmorillonite is separated from the mixed solution by filtering, and then dried at 80-100° C. for 24 hours to obtain stable modified montmorillonite.

[0046] This embodiment also provides a flame retardant composite material, comprising the modified montmorillonite and a polymer matrix, wherein the content of the polymer matrix is ​​30% of the modified montmorillonite in weight percentage.

[0047] The polymer matrix may be any one of polyethylene, polypropylene, polystyrene, polymethyl methacrylate, polyvinyl chloride, nylon, polycarbonate, and polyurethane, and polypropylene is preferred in this embodiment.

[0048] This embodiment also provides a method for preparing the flame retardant composite material. Figure 2 As shown, it includes steps S10 to S20.

[0049] Step S10: preparing a polymer matrix and modified montmorillonite.

[0050] Wherein, the content of the polymer matrix is ​​30% of the modified montmorillonite by weight.

[0051] Step S20: Mix the polymer matrix and the modified montmorillonite to prepare a flame retardant composite material by melt blending. It should be noted that the melt blending method is a conventional technical means in the art and will not be described in detail here.

[0052] The technical solution of the present application will be described in more detail below, but it should be understood that the following examples are only for explaining and illustrating the technical solution, but do not limit the scope of the present application. Moreover, unless otherwise specified, the various raw materials, reaction equipment, detection equipment and methods used in the following examples are all known in the art.

[0053] Example 1

[0054] A method for preparing a flame retardant composite material comprises steps S1 to S7.

[0055] Step S1: obtaining raw materials, which include montmorillonite, anhydrous ethanol, phosphoric acid and dodecylamine.

[0056] Step S2: adding 10 parts by weight of montmorillonite to 90 parts by weight of anhydrous ethanol solution, and stirring under the first condition to obtain a suspension.

[0057] The first condition includes: the stirring temperature is 60° C. and the stirring time is 45 min.

[0058] Step S3: adding 1.5 parts by weight of phosphoric acid to the suspension, and stirring under the second condition to obtain an activation solution.

[0059] The second condition includes: the stirring temperature is 60° C. and the stirring time is 45 min.

[0060] Step S4: adding dodecylamine to the activation solution and stirring under the third condition to obtain a mixed solution including modified montmorillonite.

[0061] The third condition includes: a stirring temperature of 60° C., a stirring time of 60 min, and a molar ratio of phosphoric acid to dodecylamine of 2.5:1.

[0062] Step S5: separating the modified montmorillonite from the mixed solution by filtration, and drying at 90° C. for 24 hours to obtain stable modified montmorillonite.

[0063] Step S6: preparing a polypropylene matrix, wherein the content of the polypropylene matrix is ​​30% of the content of the modified montmorillonite.

[0064] Step S7: Mix the polypropylene matrix and the modified montmorillonite to prepare a flame retardant composite material by a melt blending method.

[0065] Example 2

[0066] The difference from Example 1 is that the montmorillonite is 20 parts by weight, the anhydrous ethanol solution is 80 parts by weight, the phosphoric acid is 4 parts by weight, and the molar ratio of phosphoric acid to dodecylamine is 3:1.

[0067] Example 3

[0068] The difference from Example 1 is that the montmorillonite is 30 parts by weight, the anhydrous ethanol solution is 70 parts by weight, the phosphoric acid is 6 parts by weight, and the molar ratio of phosphoric acid to dodecylamine is 3.5:1.

[0069] Example 4

[0070] The difference from Example 2 is that the amount of phosphoric acid is 2 parts by weight.

[0071] Example 5

[0072] The difference from Example 2 is that the phosphoric acid is 3 parts by weight.

[0073] Example 6

[0074] The difference from Example 2 is that the amount of phosphoric acid is 3.6 parts by weight.

[0075] Example 7

[0076] The difference from Example 2 is that the amount of phosphoric acid is 4.4 parts by weight.

[0077] Example 8

[0078] The difference from Example 2 is that the amount of phosphoric acid is 5 parts by weight.

[0079] Example 9

[0080] The difference from Example 2 is that the amount of phosphoric acid is 6 parts.

[0081] Example 10

[0082] The difference from Example 2 is that the molar ratio of phosphoric acid to dodecylamine is 2:1.

[0083] Embodiment 11

[0084] The difference from Example 2 is that the molar ratio of phosphoric acid to dodecylamine is 2.5:1.

[0085] Example 12

[0086] The difference from Example 2 is that the molar ratio of phosphoric acid to dodecylamine is 2.7:1.

[0087] Example 13

[0088] The difference from Example 2 is that the molar ratio of phosphoric acid to dodecylamine is 3.2:1.

[0089] Embodiment 14

[0090] The difference from Example 2 is that the molar ratio of phosphoric acid to dodecylamine is 3.5:1.

[0091] Embodiment 15

[0092] The difference from Example 2 is that the molar ratio of phosphoric acid to dodecylamine is 4:1.

[0093] Example 16

[0094] The difference from Example 2 is that dodecylamine is replaced by silane coupling agent KH560.

[0095] Comparative Example 1

[0096] A method for preparing a flame retardant composite material comprises steps S1 and S2.

[0097] Step S1: obtaining raw materials, the raw materials comprising montmorillonite and a polypropylene matrix, wherein the content of the montmorillonite is the same as that of the modified montmorillonite in Example 1, and the content of the polypropylene matrix is ​​30% of the content of the montmorillonite.

[0098] Step S2: Mix the polypropylene matrix and montmorillonite to prepare a flame retardant composite material by melt blending.

[0099] Comparative Example 2

[0100] A method for preparing a flame retardant composite material comprises steps S1 to S7.

[0101] Step S1: obtaining raw materials, which include montmorillonite, anhydrous ethanol and phosphoric acid.

[0102] Step S2: adding 10 parts by weight of montmorillonite to 90 parts by weight of anhydrous ethanol solution, and stirring under the first condition to obtain a suspension.

[0103] Step S3: adding 1.5 parts by weight of phosphoric acid to the suspension, and stirring under the first condition to obtain an activation solution.

[0104] The first condition includes: the stirring temperature is 60° C. and the stirring time is 45 min.

[0105] Step S4: separating the modified montmorillonite from the activation solution by filtration, and drying at 90° C. for 24 hours to obtain stable modified montmorillonite.

[0106] Step S5: preparing a polypropylene matrix, wherein the content of the polypropylene matrix is ​​30% of the content of the modified montmorillonite.

[0107] Step S6: Mix the polypropylene matrix and the modified montmorillonite to prepare a flame retardant composite material by a melt blending method.

[0108] Comparative Example 3

[0109] A method for preparing a flame retardant composite material comprises steps S1 to S7.

[0110] Step S1: obtaining raw materials, which include montmorillonite, anhydrous ethanol and dodecylamine.

[0111] Step S2: adding 10 parts by weight of montmorillonite to 90 parts by weight of anhydrous ethanol solution, and stirring under the first condition to obtain a suspension.

[0112] Step S3: adding dodecylamine to the suspension and stirring under the second condition to obtain an activated solution, wherein the amount of dodecylamine added is the same as that in Example 1.

[0113] The second condition includes: the stirring temperature is 60° C. and the stirring time is 60 min.

[0114] Step S4: separating the modified montmorillonite from the activation solution by filtration, and drying at 90° C. for 24 hours to obtain stable modified montmorillonite.

[0115] Step S5: preparing a polypropylene matrix, wherein the content of the polypropylene matrix is ​​30% of the content of the modified montmorillonite.

[0116] Step S6: Mix the polypropylene matrix and the modified montmorillonite to prepare a flame retardant composite material by a melt blending method.

[0117] In order to verify the performance of the product of the present application, the flame retardant composite materials of the embodiments and comparative examples were subjected to hydrophobicity tests and flame retardancy tests. The test results are shown in Table 1.

[0118] (1) Hydrophobicity test: The water contact angle of the flame retardant composite material was tested by a water drop angle tester.

[0119] (2) Flame retardancy test: The flame retardant composite materials were subjected to limiting oxygen index (LOI) test and UL-94 vertical burning test.

[0120] Table 1: Hydrophobicity and flame retardancy test data of flame retardant composite materials of Examples and Comparative Examples

[0121]

[0122]

[0123] It can be seen from the above test results that the thermal conductive gasket of the present application has at least the following beneficial effects: the water contact angle is at least 95°, and it has good hydrophobicity; the limiting oxygen index is at least 29%, the flame retardant grade is V-0, and it has good flame retardant properties.

[0124] It can be seen from Examples 2, 5 and 6 that when the amount of phosphoric acid added is 15% to 20% of the montmorillonite content, as the phosphoric acid content increases, the water contact angle gradually increases to above 105°; the limiting oxygen index gradually increases to above 35%, and the flame retardant grade is stabilized at V-0.

[0125] It can be seen from Examples 2, 7 and 8 that when the amount of phosphoric acid added is 20% to 25% of the montmorillonite content, as the phosphoric acid content increases, the water contact angle gradually decreases, but is also stable at above 104°; the limiting oxygen index gradually decreases and stabilizes at above 35%, and the flame retardant grade is stable at V-0.

[0126] It can be seen from Examples 4-5 that when the phosphoric acid content is too low, less than 15%, the water contact angle will decrease to only 95°; the limiting oxygen index will decrease to only 29%.

[0127] It can be seen from Examples 8-9 that when the phosphoric acid content is too high, higher than 25%, the water contact angle will decrease to 97°; and the limiting oxygen index will decrease to 30%.

[0128] It can be seen from Examples 2, 11 and 12 that when the molar ratio of phosphoric acid to dodecylamine is 2.5:1 to 3:1, as the molar ratio increases, the water contact angle gradually increases to above 106°; the limiting oxygen index gradually increases to above 35%.

[0129] It can be seen from Examples 2, 13 and 14 that when the molar ratio of phosphoric acid to dodecylamine is 3:1 to 3.5:1, as the molar ratio increases, the water contact angle gradually decreases, but also stabilizes above 106°; the limiting oxygen index gradually decreases and stabilizes above 34%.

[0130] It can be seen from Examples 10-11 that when the molar ratio is less than 2.5:1, the water contact angle decreases to only 96°, and the limiting oxygen index decreases to 30%.

[0131] It can be seen from Examples 14-15 that when the molar ratio is greater than 3.5:1, the water contact angle decreases to 97°, and the limiting oxygen index decreases to 30%.

[0132] By comparing Example 2 and Example 15, it can be seen that compared with the silane coupling agent KH560, when dodecylamine is used, the water contact angle and limiting oxygen index of the material are higher, and the hydrophobicity and flame retardancy are significantly enhanced.

[0133] It can be seen from Comparative Examples 1-3 that adding phosphoric acid or dodecylamine to modify montmorillonite alone can enhance the hydrophobicity and flame retardant properties of the material.

[0134] It can be seen from Example 1 and Comparative Examples 2-3 that the synergistic modification of montmorillonite by adding phosphoric acid and dodecylamine simultaneously can significantly enhance the hydrophobicity and flame retardant properties of the material.

[0135] In the present application, the best embodiment is embodiment 2, the water contact angle reaches 110°, the limiting oxygen index reaches 38%, the flame retardant grade is V-0, and the hydrophobicity and flame retardancy are the best.

[0136] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, substitute and modify the above embodiments within the scope of the invention without departing from the principles and purpose of the present invention. All such changes should fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing modified montmorillonite, characterized in that: include: Obtaining raw materials, wherein the raw materials at least include montmorillonite, ethanol, phosphoric acid and dodecylamine; Adding the montmorillonite to ethanol and stirring under a first condition to obtain a suspension; adding the phosphoric acid to the suspension and stirring under two conditions to obtain an activated solution; adding dodecylamine to the activation solution and stirring under a third condition to obtain a mixed solution including modified montmorillonite; The modified montmorillonite is separated from the mixed solution.

2. The preparation method according to claim 1, characterized in that: In terms of weight percentage, the content of the montmorillonite is 10wt% to 30wt%, and the content of the ethanol is 70wt% to 90wt%.

3. The preparation method according to claim 2, characterized in that: The added amount of the activator is 15% to 25% of the montmorillonite content.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the phosphoric acid to the dodecylamine is 2.5:1 to 3.5:

1.

5. The preparation method according to claims 1-4, characterized in that: The first condition includes: a stirring temperature of 50 to 70° C. and a stirring time of 30 to 60 min.

6. The preparation method according to claims 1-4, characterized in that: The second condition includes: a stirring temperature of 50 to 70° C. and a stirring time of 30 to 60 min.

7. The preparation method according to claims 1-4, characterized in that: The third condition includes: a stirring temperature of 50 to 70° C. and a stirring time of 30 to 60 min.

8. A flame retardant composite material, characterized in that: The invention comprises modified montmorillonite and a polymer matrix, wherein the content of the polymer matrix is ​​30% of the modified montmorillonite by weight, and the modified montmorillonite is prepared by the preparation method according to any one of claims 1 to 7.

9. A method for preparing a flame retardant composite material, characterized in that: include: Prepare a polymer matrix and the modified montmorillonite obtained by any one of the preparation methods of claims 1 to 7; The polymer matrix and the modified montmorillonite are mixed to prepare a flame retardant composite material by a melt blending method; In terms of weight percentage, the content of the polymer matrix is ​​30% of the content of the modified montmorillonite.